2014
DOI: 10.1186/1746-1596-9-107
|View full text |Cite
|
Sign up to set email alerts
|

Adult type granulosa cell tumor of the testis with a heterologous sarcomatous component: case report and review of the literature

Abstract: Adult testicular granulosa cell tumors are rare sex cord- stromal tumors of which only 45 have been previously reported. As compared with their ovarian counterparts, these tumors may follow a more aggressive course because the proportion of malignant cases is higher. We report here a unique case of a 78-year Caucasian with a left sided adult type granulosa cell tumor with a heterologous sarcomatous tumor component. A heterologous sarcomatous component has occasionally been observed in ovarian tumors but never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
0
19
1
Order By: Relevance
“…On ommunohistochemical examination, adenocarcinoma cells are positive for epithelial membrane antigen and cytokeratin. [18] …”
Section: Discussionmentioning
confidence: 99%
“…On ommunohistochemical examination, adenocarcinoma cells are positive for epithelial membrane antigen and cytokeratin. [18] …”
Section: Discussionmentioning
confidence: 99%
“…The adult-type GCT is extremely rare in the testis, Schubert et al [35] have found 43 cases in the literature [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] and we were able to find three more recent cases in PubMed ( Table 1 ) [2] , [36] . However, in most of the reports these tumours are only the object of immunohistochemical or cytogenetic investigations; thus, the clinical data are missing partially [5] , [11] , [22] , [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Macrofollicles ought to be present and the presence of the Call-Exner bodies facilitates the correct diagnosis; however, they are not always found and thus, are not indispensable to diagnosis 2. Granulosa cells should represent the biggest part of the tumour.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular invasion, infiltrative margins, necrosis, atypical mitotic figures and high mitotic index can be associated with malignancy, but as single criteria they are not predictive 2. The only reliable predictor of malignancy in GCT, as in all other stromal tumours, is a diameter >5 cm 4…”
Section: Introductionmentioning
confidence: 99%